Effectiveness of OpenSID Application in Improving Services in Kemamang Village Bojonegoro - Septianingrum, Diyenik Eka; Oktariyanda, Trenda Aktiva (SERUNAI, 2023)
The Bojonegoro District Government, together with the Bojonegoro District Communication and Information Office (KOMINFO), had implemented the use of the OpenSID application as a means of providing better public services. One of the areas where this initiative was being carried out was in Kemamang Village, Balen Sub-district, Bojonegoro District. The objective of this research was to describe the Effectiveness of Implementing the OpenSID Application in Improving Document Services in Kemamang Village. This study employed a qualitative descriptive research method, focusing on effectiveness measurement based on Subagyo’s criteria, which included program targeting accuracy, program socialisation, program goal achievement, and program monitoring. The research findings indicated that the OpenSID programme in Kemamang Village had effectively achieved its goals and objectives. OpenSID had facilitated access and enhanced citizen satisfaction. However, the programme’s socialisation aspect had not been effective, leading to low citizen participation. Intensive socialisation involving the community was necessary. Programme monitoring needed enhancement to identify issues and improve programme quality. The challenge of application maintenance also required attention to ensure programme performance. By undertaking these measures, the OpenSID programme could become more effective and optimal. The implementation of the OpenSID application in Kemamang Village was ineffective in terms of the socialisation and programme monitoring indicators. The lack of citizen engagement in socialisation had resulted in a lack of awareness regarding document creation requirements. Therefore, the Village Government needed to actively participate in planned socialisation methods. Ineffective monitoring has also led to system maintenance issues. Therefore, the Village Government should conduct regular monitoring to address problems and enhance programme effectiveness.